Nongovernmental organizations as interest groups and their roles in policy processes: Insights from Indonesian forest and environmental governance - Laraswati, Dwi; Krott, Max; Soraya, Emma; Rahayu, Sari; Fisher, Micah R.; Giessen, Lukas; Maryudi, Ahmad (Forest and Society, 2022)
The traditional conceptions and claims of nongovernmental organizations (NGOs) have profiled NGOs as civil society representatives and as benevolent philanthropic actors of development in the Global South. However, recent phenomena indicate NGOs often acting in opposition to their benevolent claims. This study attempts to move away from the normative concepts of NGOs and develop an analytical framework fitted with the current empirics in environmental governance. Using theories of organized interest groups in a democratic political system, we analyze the extent of NGOs fulfilling their roles as organized interest groups (OIGs), where they should take roles representing the interests of particular groups within societies and exerting political influence on governments on the basis of these common interests. We use empirics from Indonesian forest and environment-related governance, and our framework is called “Representation–Influence Framework,” which assists in establishing more systematic coherent typologies of OIGs. Analyzed from the perspective that NGOs claim to serve as representatives of specific groups within societies, we establish three overarching categories of OIGs, that is, 1) en route to fulfilling the claim, 2) breaking the claim, and 3) opposing the claim. We further detail our framework into a subset of nine OIG typologies. In this way, we provide pathways to begin deconstructing the common simplifications and misunderstandings about NGOs. For empirics, we identified 38 OIGs in the cases of social forestry and timber legality policies and populated them according to the typologies. We found that most of them are en route to fulfilling the claim of representing the groups’ interests, although their political influence on the government is, in most cases, limited.